2020
DOI: 10.1111/1751-7915.13629
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Lactobacillus salivarius Li01 on thioacetamide‐induced acute liver injury and hyperammonaemia

Abstract: The gut microbiota plays pivotal roles in liver disease onset and progression. The protective effects of Lactobacillus salivarius Li01 on liver diseases have been reported. In this study, we aimed to detect the protective effect of L. salivarius Li01 on thioacetamide (TAA)-induced acute liver injury and hyperammonaemia. C57BL/6 mice were separated into three groups and given a gavage of L. salivarius Li01 or phosphate-buffered saline for 7 days. Acute liver injury and hyperammonaemia were induced with an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…However, very few studies have been conducted that examine the dose-response relation. Therefore, based on the research of Yang et al ( 29 ), the protective effect of different concentrations of L. salivarius Li01 on TAA-induced acute liver injury and hyperammonemia was explored in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, very few studies have been conducted that examine the dose-response relation. Therefore, based on the research of Yang et al ( 29 ), the protective effect of different concentrations of L. salivarius Li01 on TAA-induced acute liver injury and hyperammonemia was explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found the overall trend of ammonia levels in intestinal contents and blood to decrease with the increase of intervention concentration of Lactobacillus salivarius Li01. Yang et al proved that L. salivarius Li01 reduced fecal ammonia, and a correlation has been established between the concentrations of blood ammonia, fecal ammonia, and fecal microbiota ( 29 ). This study demonstrated that pretreatment of mice with different concentrations of L. salivarius Li01 leads to different amounts of L. salivarius Li01 colonizing their lumen, changes the composition and function of intestinal microbial structure, and therefore, affects their intestinal ammonia metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations